Greasing the Wheels of Rural Transformation? Margarine and the Competition for the British Butter Market - Markus Lampe; Paul Sharp (European Historical Economics Society (EHES), 2013)
We consider an example of the impact of a new good on producers of close substitutes: the invention of margarine and its rapid introduction into the British market from the mid-1870s. This presented a challenge to the traditional suppliers of that market, butter producers from different European countries. We argue that the capacity to react quickly to the appearance of this cheap substitute by improving quality and establishing product differentiation was critical for the fortunes of butter producers. We illustrate this by discussing the different reactions to margarine and quality upgrading in Ireland, Denmark and the Netherlands. A statistical analysis using monthly data for Britain from 1881-87 confirms that margarine had a greater impact on the price of poor quality butter than that of high quality butter, presumably because it was a stronger substitute.
Keywords: L66; N53; O31; 330; Butter; margarine; dairies; new products; quality changes